Periodic Solutions for a Numerical Discretization Neural Network - Chun Lu (Discrete Dynamics in Nature and Society)
The existence and global exponential stability of periodic solutions for a class of numerical discretization neural networks are considered. Using coincidence degree theory and Lyapunov method, sufficient conditions for the existence and global exponential stability of periodic solutions are obtained. Numerical simulations are given to illustrate the results.